The Address Terms Based on Kinship System of Malay Found in Kabupaten Sarolangun Jambi - Istiqomah, Putri; Jufrizal, Jufrizal (English Language and Literature, 2021)
This research aimed to find out types of address terms based on kinship system and the differences of address terms based on culture and value based on kinship system of Malay found in Kabupaten Sarolangun Jambi. This research is descriptive qualitative research. The object of these research are17 participants with 55 recorded conversations.  The data gather by interview and recording of the source conversation. These data were gather and transcript as the instrument to be analyzed about address terms found in Kabupaten Sarolangun. The research data were gained in the form of interpretations of participant recorded conversations and interviews. Based on data analysis, it was found that in Kabupaten Sarolangun, people use address in everyday life such as in conversation, meeting, letter, messages. Most people address their friends and their families  are differently from those they do not know so well, and from those who are in a superior relationship to them such as the school or the boos at work. The type of address found in Kabupaten Sarolangun are : Title and Last Name (TLN), First Name (FN), Title only (T), Last Name (Last Name), Special Nickname, (SN) Special Name, and Kinship Term (KT).  It also found that people in Kabupaten Sarolangu Jambi have different kinds of address based on culture ad value. Furthermore, Each of address and the difference of the usage of address in Kabupaten Sarolanun bring   the relation between the speaker and the listener.